Aplicação de ferramentas do Lean Manufacturing para redução de perdas em um posto de preparação para pintura de máquinas elétricas - Hernachi, Lucinei (2020)
The continuous pursuit for coast reduction in productive process has been the focus of most companies that manage to increase their competitiveness. The continuous improvement has been used in the corporations through several management tools and nowadays has a strategic role for the big corporations. The application of tools for losses and waste, resources optimization and non-value-adding activities has brought some significant gains in productivity and financial amounts to the companies. The Lean Manufacturing approach present itself as one of these management tools whose core objective is to create value, cutting the wastes in order to involve the company in a customer-orientated continuous improvement culture. This research-project was carried out with the objective to apply concepts and Lean Manufacturing tools, in order to improve the productivity and eliminate non-value-adding activities in a painting shop workstation for electrical machines in a big company in the north of the state of Santa Catarina (BR). With these actions developed and tested in the workplace, it was possible to propose any changes in the current methods used in this workplace and after observing the gains in standardization in the preparation and painting activities, elimination of activities that do not add value, reduction of waiting times, reduction of movements with overhead crane and reduced people movements. The application of these new method in the preparation of the workstation points to an increase of productivity of 7%, going from 60% to 67% in the workplace and an annual financial benefit of approximately R$ 51.375,00. With all these, the result of the research was considered satisfactory and it´s application is perfectly doable. As it is a researching-action, it highlights the need and involvement of people for the success of the study.